A Comparative Case-Based Study on Age-Related Differences in Angular Velocity During Isokinetic Strength Assessments Based on Individual Capacity - Yu, JaeHo (Journal of Neonatal Surgery, 2025)
This study aims to elucidate the relationship between chronological aging and neuromuscular performance by comparing isokinetic strength parameters across different age groups. Specifically, it investigates how the individualized angular velocity settings during isokinetic knee extension and flexion exercises influence performance metrics such as peak torque, total work, and average power in both younger and older adults. The participants included individuals in their 20s and 60s, representing the early and late stages of adult musculoskeletal aging. Using an isokinetic dynamometer, measurements were collected at 10%, 40%, 70%, and 100% of each participant’s maximum angular velocity. The findings consistently demonstrated that the older group showed significantly reduced performance across all measured variables, implying a decline in skeletal muscle function with advancing age. This pattern was evident even after normalizing for individual capabilities, suggesting that intrinsic neuromuscular limitations become more pronounced with age. The implications of these findings are multifold: they reinforce the necessity for age-sensitive velocity modulation during resistance training and underscore the importance of personalized rehabilitation programs for elderly populations. Furthermore, this study provides foundational data for clinicians and exercise specialists seeking to optimize functional outcomes through velocity-specific interventions. Future research should incorporate larger samples and include electromyographic and metabolic markers to further elucidate the mechanisms driving age-related declines in isokinetic performance.